"Girls Behaving Badly?" Young Female Violence in New Zealand - Lynch, Nessa (Victoria University of Wellington Law Review, 2014)
While female crime, and particularly young female violence, has long been a titillating subject for the media, recent reports suggest an upsurge in violence amongst girls in New Zealand. This short article uses raw apprehension and sentencing data to consider the question of whether violence by girls is indeed increasing. It is concluded that while there does seem to have been an increase in violence by girls in the earlier part of the decade, the level of violence has fallen in the last three years. There may also be other explanations for an increase in apprehensions for violent offences such as changes in Police practice and societal attitudes.